Da’wah and Local Wisdom: Content Analysis of Da’wah Value in Wawacan Ma’dani Al-Mu’allim (WMM) - Rohanda, Rohanda (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
The purpose of this study is to present and describe the values of local wisdom based on the inner structure of the meaning of Wawacan Madani al-Mu'allim (WMM) and the intertextual relations with other texts as the hypogram text. The method used in this research is the content analysis method (tahlÄ«l al-madhmÅ«n) with the intertextuality approach of Riffatere's semiotic model. The research results show that WMM's wawacan script contains local wisdom values related to life and life. The WMM text has an intertextual relationship with previous texts, for example, with the Koran, Hadith, and Al-Ghazali's Bidayatul Hidayah book as the hypogram text or its reference source. The WMM manuscript contains teachings related to local wisdom values: live a simple, religious life, abstain from disgraceful acts, maintain personal and environmental hygiene, improve transcendental communication networks, and maintain a clean heart (tazkiyah an-qalbi), and everything has its uniqueness. The text and contents of the WMM manuscript have an intertextual relationship with the al-Qur'an, al-Hadith, and al-Ghazali's book Bidayat al-Hidayah.